TOTAL Escherichia coli PADA SOSIS IKAN YANG DI-COATING DENGAN MIOFIBRIL ASAP CAIR SELAMA PENYIMPANAN - Keno, Jupni; Dien, Henny Adeleida; Agustin, Agnes Triasih (Media Teknologi Hasil Perikanan, 2016)
Fish sausages are prepared foods that have a high nutritional value, but that is the weakness of this commodity is rapidly decaying nature. Bacterial pathogens that must be avoided include Escherichia coli. These bacteria are gram-negative, rod-shaped and motile spores are not. The purpose of this study is to calculate the total coliforms and E. coli in fish sausage coating of fish protein myofibrils Black Marlin (Makaira indica) during storage at room temperature (28–29°C), and refrigerator temperature (10–13°C). The method used is descriptive method, which is a study conducted to analyze an individual, the state, or the symptoms of a particular group. The results showed that the total coliform in fish sausage in coating with liquid smoke is stored at room temperature, the lowest value is 7 MPN/g, the highest of 120 MPN/g, while the lowest value refrigerator temperature is 7 MPN/g, the highest 93 MPN/g. Total coliform in fish sausage in smokeless liquid coating stored at room temperature with the lowest value is 7 MPN/g, the highest 210 MPN/g, while the lowest value refrigerator temperature is 7 MPN/g, and the highest is 120 MPN/g. Total coliform in fish sausages are not in the coating deposited at room temperature with the lowest value is 7 MPN/g, the highest of 240 MPN/g, at refrigerator temperature the lowest value is 7 MPN/g, and the highest is 150 MPN/g. Total E. coli showed that the fish sausage in coating with liquid smoke is stored at room temperature, the lowest value is 1 MPN/g, and the highest is 4 MPN/g, while the lowest value refrigerator temperature is <3 MPN/g, and The highest is 3 MPN/g. Total E. coli in fish sausage in smokeless coating liquid stored at room temperature, the lowest value is 2 MPN/g, and the highest is 4 MPN/g, while the temperature of the refrigerator lowest value is 1 MPN/g, and a high of 3 MPN/g. Total E. coli in sausages are not in the coating deposited at room temperature, the lowest value is 2 MPN/g, and the highest is 5 MPN/g, and the refrigerator temperature is the lowest rating 2 MPN/g, the highest is 4 MPN/g during storage .Keywords: fish sausage, coating, myofibril, Eschericia coli.  Sosis ikan merupakan makanan siap saji yang mempunyai nilai gizi tinggi, namun yang menjadi kelemahan dari komoniti ini adalah sifatnya yang cepat membusuk. Bakteri patogen yang harus dihindari antara lain Escherichia coli.  Bakteri ini bersifat gram negatif, berbentuk batang tidak spora dan bersifat motil. Tujuan penelitian ini yaitu untuk menghitung total koliform dan E. coli pada sosis ikan yang dicoating dari miofibril protein ikan Black Marlin (Makaira indica) selama penyimpanan suhu ruang (28–29°C), dan suhu kulkas (10–13°C). Metode penelitian yang digunakan adalah metode deskriptif, yaitu suatu penelitian yang dilakukan untuk menganalisa suatu individu, keadaan, gejala atau kelompok tertentu. Hasil penelitian menunjukkan bahwa total koliform pada sosis ikan yang dicoating dengan asap cair disimpan pada suhu ruang, nilai terendah yaitu 7 MPN/g, tertinggi 120 MPN/g, sedangkan pada suhu kulkas nilai yang terendah yaitu 7 MPN/g, tertinggi 93 MPN/g. Total koliform pada sosis ikan yang dicoating tanpa asap cair disimpan pada suhu ruang dengan nilai terendah yaitu 7 MPN/g, tertinggi 210 MPN/g, sedangkan pada suhu kulkas nilai yang terendah yaitu 7 MPN/g, dan tertinggi 120 MPN/g. Total koliform pada sosis ikan tidak dicoating disimpan pada suhu ruang dengan nilai terendah yaitu 7 MPN/g, tertinggi 240 MPN/g , pada suhu kulkas nilai terendah yaitu 7 MPN/g , dan tertinggi 150 MPN/g. Total E. coli menunjukkan bahwa pada sosis ikan yang dicoating dengan asap cair disimpan pada suhu ruang, yaitu nilai terendah 3 MPN/g, dan tertinggi 4 MPN/g, sedangkan pada suhu kulkas nilai terendah yaitu <3 MPN/g, dan tertinggi 3 MPN/g. Total E. coli pada sosis ikan yang dicoating tanpa asap cair disimpan pada suhu ruang, yaitu nilai terendah 3 MPN/g, dan tertinggi 4 MPN/g, sedangkan pada suhu kulkas nilai terendah yaitu <3 MPN/g , dan tertinggi 3 MPN/g. Total E. coli pada sosis tidak dicoatingdisimpan pada suhu ruang, yaitu nilai terendah 4 MPN/g, dan tertinggi 7 MPN/g, dan pada suhu kulkas yaitu nilai terendah 3 MPN/g, tertinggi 4 MPN/g selama penyimpanan.Kata kunci: sosis ikan, coating, myofibril, Eschericia coli.